Petrography and Physicomechanical Characteristics of Iyuku Granite, Southwestern Nigeria - Ugbe, Felix Chukwuka (Iraqi Journal of Science, 2020)
Petrography and physicomechanical characteristics of Iyuku granite from southwestern Nigeria were investigated. Rock and aggregate samples were obtained from five different quarry sites for thin-sectioning and physical and mechanical tests. The rock slides were subjected to petrographic analysis, while the aggregates were tested for the parameters of specific gravity (S.G), water absorption, aggregate impact value (AIV), aggregate crushing value (ACV), Los Angeles abrasion value (LAAV), and flakiness and elongation indices in accordance with the British Standards (B.S), American Standards for Testing Materials (ASTM) and Federal Ministry of Works Standards (FMWS). The petrographic, physical, and mechanical characteristics were described by bar charts and linear graphs. The results revealed that the rocks are of medium to coarse interlocking grains, with no evidence of weathering influences, and quartz content ranging from 17% to 35%. The aggregates showed appreciable high S.G. values, very low water absorption values and low maximum permission limits for AIV, ACV and LAAV when compared with different standards. All the aggregates are adjudged to be generally strong and durable for road construction, but those with higher quartz contents are more preferable. Significant statistical correlations were established among both physical and mechanical tests conducted.